IDSpoof: intrusion detection to detect malware / Muhammad Khairie Ismail - Ismail, Muhammad Khairie (2020)
Nowadays, people all over the world like to store their data over the Internet because it is easy for them to retrieve and store it. Unfortunately, they are exposed to the cyber-crime like data theft because of the lack of security in their device. People usually did not have a security tool for their network. To prevent data theft, we need to monitor and identify the packet, which is appropriate in the network. It is important to prevent the malicious packet from going through the network because it may affect the privacy’s data of the user. IDSpoof was developed to monitor the network packet and expected to have the functionality of the system. The methodology was used to develop the project using research framework. After this project is developed, the IDSpoof is expected to be used by the user and the result demonstrate successful decrement of data theft among the user. Then, user network will be more secured and protectable.